A simple HPLC—UV method for simultaneous determination of cysteine and cysteinylglycine in biological fluids - Głowacki, R.; Stachniuk, J.; Borowczyk, K. (Acta chromatographica, 2016)
A new and simple method based on high-performance liquid chromatography with ultraviolet detection (HPLC-UV) for the determination of cysteine (Cys) and cysteinylglycine (CysGly) in plasma and urine has been developed. The method involves reduction of disulfide bonds with tris(2-carboxyethyl)phosphine, derivatization of the analytes with 2-chloro-1-methylquinolinium tetrafluoroborate, and separation on Aeris PEPTIDE XB-C18 column (150 mm × 4.6 mm, 3.6 μm, Phenomenex) with UV detection at 355 nm. The calibration lines, obtained with human plasma and urine spiked with Cys- Gly and Cys, were linear in the range of 2.5–50 μmol L −1 and 20–300 μmol L −1 , respectively. The intra- and inter-day precision values of the method, expressed as a relative standard deviation, were 0.25–11.1% and 0.71–12.3%, respectively. The analytical recovery varied from 89.7 to 112.3%. The LOQs for total Cys and CysGly were 1.5 pmol and 2.3 pmol in peak, respectively. The method was successfully applied to samples donated by apparently healthy individuals. Concentrations of Cys and CysGly in human plasma from 18 subjects varied from 141.6 to 217.8 μmol L −1 and from 21.1 to 50.9 μmol L −1 , respectively. Their concentrations in urine samples ( n = 14) ranged from 137.3 to 426.8 μmol L −1 and from 1.6 to 4.9 μmol L −1 , respectively.